Was Al-Shafi'i Against Al-Masalih Al-Mursalah? - Wan Ahmad, Wan Azhar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Was Al-Shafi'i Against Al-Masalih Al-Mursalah?